2017
DOI: 10.1111/fog.12245
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity in the diel vertical movement of two pelagic predators (Prionace glauca and Alopias vulpinus) in the southeastern Indian Ocean

Abstract: Management and conservation of marine predator species relies on a fundamental knowledge of their movements and behaviour. Pop‐up satellite archival tags were used to investigate the vertical movement patterns of five blue sharks (Prionace glauca) and one thresher shark (Alopias vulpinus) within the southeastern Indian Ocean. Sections of similar depth distribution, identified using a split moving window analysis, were investigated in relation to the thermal structure of the water column and activity rates. Min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 72 publications
(141 reference statements)
0
6
0
Order By: Relevance
“…It is worth noting that latitudinal species shifts in response to warming can be misleading with some pelagic species migrating vertically not latitudinally (Perry et al, 2005;Beaugrand and Kirby, 2018) and this may be the case with some pelagic shark species. In Australian waters, pelagic sharks have been recorded regulating their depth to occupy regions of favorable temperatures, although this behavior could also be related to prey movements (Rogers et al, 2009;Stevens et al, 2010;Heard et al, 2017) as well as habitat suitability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth noting that latitudinal species shifts in response to warming can be misleading with some pelagic species migrating vertically not latitudinally (Perry et al, 2005;Beaugrand and Kirby, 2018) and this may be the case with some pelagic shark species. In Australian waters, pelagic sharks have been recorded regulating their depth to occupy regions of favorable temperatures, although this behavior could also be related to prey movements (Rogers et al, 2009;Stevens et al, 2010;Heard et al, 2017) as well as habitat suitability.…”
Section: Discussionmentioning
confidence: 99%
“…The Australian Exclusive Economic Zone (EEZ) is already being impacted by climate change with waters off south-east Australia warming at almost four times the global average (Oliver et al, 2017) and range extensions already documented in several fish species (Last et al, 2011). Australia has one of the world's most diverse communities of sharks, with 182 recognized species (Simpfendorfer et al, 2019), and SST has been shown consistently to be a strong predictor of pelagic shark occurrence in Australian waters (Rogers et al, 2009(Rogers et al, , 2015Stevens et al, 2010;Heard et al, 2017;Birkmanis et al, 2020). It is therefore important to investigate the likely impact of temperature changes on pelagic shark distribution and the location of suitable habitat on a continental scale if these species are to be appropriately managed into the future -especially if such changes may require a reassessment of interactions with fisheries in the future.…”
Section: Introductionmentioning
confidence: 99%
“…Although probably not high conservation priorities for the IOTC, it is possible that some of these species are caught in tuna gears. The Indian Ocean contains numerous seamounts that are relatively shallow, and where many elasmobranchs make diurnal migrations through wide ranges of the water column, making them simultaneously epipelagic, mesopelagic and bathypelagic (Heard, Rogers, Bruce, Humphries, & Huveneers, 2018; Sims et al, 2006; Speed, Field, Meekan, & Bradshaw, 2010; WWF, 2020). The encounterability attribute could be improved by estimating the distribution of species and fishing effort throughout the depth range, at least by the susceptibility group (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the effect of climate change due to the physiological and biological characteristics of the species, their shifts in distribution could be related to their biological interactions with other organisms (Gervais et al, 2020), since the first response of species to altered environmental conditions is to adjust their behavior (Wong and Candolin, 2015). One such adjustment is distribution shifts in apex predators such as the large sharks (Heard et al, 2017) because novel combinations of prey species could generate reorganization of species, even among the trophic webs (Lurgi et al, 2012;Cameron et al, 2019). It has also been observed that expansion of the distribution range is dominated by dietary generalist species (Evans and Moustakas, 2018;Bartley et al, 2019).…”
Section: Discussionmentioning
confidence: 99%